Role of receptor kinase in short-term desensitization of cardiac muscarinic K(+) channels expressed in Chinese hamster ovary cells - Shui, Z (Blackwell Science Inc, 1998)
1. The cardiac muscarinic receptor–K(+) channel system was reconstructed in Chinese hamster ovary (CHO) cells by transfecting the cells with the various components of the system. The activity of the muscarinic K(+) channel was measured with the cell-attached configuration of the patch clamp technique. 2. In CHO cells transfected with the channel (Kir3.1/Kir3.4), receptor (hm2) and receptor kinase (GRK2), on exposure to agonist, there was a decline in channel activity as a result of desensitization, similar to that in atrial cells. 3. Whereas the desensitization was almost abolished by not transfecting with the receptor kinase or by transfecting with a mutant receptor lacking phosphorylation sites, it was only reduced (by ≈39 %) by transfecting with a mutant receptor kinase with little kinase activity. 4. These results suggest that the receptor kinase is responsible for desensitization of the muscarinic K(+) channel and that this involves phosphorylation-dependent and -independent mechanisms.